Investigation on contact and bending stress of face-hobbed and face-milled hypoid gear. (August 2020) - Liu, Siyuan; Song, Chaosheng; Zhu, Caichao; Liang, Chengcheng; Bai, Huan
Highlights: The load capacity of face-hob bed and face-milled hypoid gear have been researched. Finite element analysis methods and strength check from international standards were conducted. The statistical method was used to assess the contact and bending stress of gear flank. The contact area with high contact stress for face-milled hypoid gear is larger than those of face-hob bed gear. The strength check results and finite element analysis results can verify with each other consistently. Abstract: The tooth strength performance of face-hobbed and face-milled hypoid gears under the same work condition is a controversial research hotspot. In this paper, the load capacity of face-hobbed and face-milled hypoid gears has been studied based on finite element analysis method and conventional international standards. The stress comparison for contact and bending stress between two types of gears have been conducted. The accurate mathematical model of face-hobbed and face-milled hypoid gear were established based on the generating and forming process. The statistical method was used to assess the contact and bending stress. Results show that the values of bending stress of face-milled gear are about 20–30% larger than those of face-hobbed gear. For the contact area with high stress (800–1300 MPa), the proportion of face-milled hypoid gear is much more than that of face-hobbed gear. The standard deviation values of contact point stress for face-milled hypoid gear are 7.1% higher than those of face-hobbed gear. The strength results by standards and finite element analysis results can verify with each other consistently. Both results contribute that face-hobbed hypoid gear has better tooth strength under the same condition.